Risk management and the complexity of the right to refuse dangerous work in the context of hospital care: Preliminary issues. - Calvo, Daniel de Souza Costa; Ferreira, João Alberto; Cunha, Daisy Moreira; Mendes, Davidson Passos (Work, 2020)
BACKGROUND: Risk management analysis at work makes it possible to find individual and collective experiences of recognition and hierarchization of risks in view of the specificities of labor situations and the complex and contradictory application of the right to refuse in health work, whose space and technique are still in a deep structural transformation. OBJECTIVE: To investigate how work organization impacts on the daily life of nursing care, in a general hospital surgical center, (un)enabling individual and collective risk management strategies in the context analyzed and how the right to refuse can be appropriate as a condition and strategy for work management. METHODS: Ergonomics (Work Ergonomic Analysis) was used to bring about the actual work activity and Ergology for epistemological deepening, whose research approach took place in a surgical center with four registered nurses. RESULTS: The results reveal that nursing work is invisible and that individual and collective strategies are used to manage the variability and constraints of the environment. The right to refuse is one of the competencies universe strategies conceived and built at work that ensure the realization of the results found. CONCLUSIONS: The right to refuse is full of meanings. Refusing does not mean "not doing", but also to do otherwise, by other means. It is beyond health and security and can be linked to other variables such as quality, environment, social responsibility.